1983
DOI: 10.1038/304371a0
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of human apolipoproteins A-I and C-III genes

Abstract: It has recently been suggested that polymorphisms in the human apolipoprotein A-I (apo A-I) gene locus may be related to the development of premature atherosclerosis and hypertriglyceridaemia. To understand if and how these polymorphisms affect apo A-I gene expression, we studied the genomic sequences flanking the apo A-I gene. Here we show the presence of another apolipoprotein gene, apolipoprotein C-III (apo C-III), approximately 2.6 kilobases (kb) downstream of the 3' end of the apo A-I gene. We also show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(57 citation statements)
references
References 20 publications
2
54
0
1
Order By: Relevance
“…A genomic clone containing both APOAJ and APOC3 was isolated and characterized, and the results indicated that the genes are oriented 3' to 3' and are separated by about 3 kb of intergenic DNA (56). This contrasts with the tandem (3' to 5') orientation of APOE and APOCJ (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…A genomic clone containing both APOAJ and APOC3 was isolated and characterized, and the results indicated that the genes are oriented 3' to 3' and are separated by about 3 kb of intergenic DNA (56). This contrasts with the tandem (3' to 5') orientation of APOE and APOCJ (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…The apo CIII Sst-I polymorphism arises from a C-G transversion in the 3' noncoding region of the apo CIII gene (Karathanasis et al, 1983). The apo AI Msp-I polymorphism arises from the presence or absence of a Msp-I site in the third intron of the apo AI gene (Seilhamer et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The human apo AI and apo CIII genes are tightly linked and form a gene complex together with the apo AIV gene on the long arm of the chromosome 11 (Karathanasis et al, 1983;Law et al, 1984;Cheung et al, 1984;Karathanasis, 1985;Elshourbagy et al, 1986). Restriction fragment length polymorphisms related to the apo AI and apo CIII genes have been reported to be associated with coronary atherosclerosis in Caucasians (Ferns et al, 1985;Rees et aI., 1985;Ferns and Galton, 1986;Ordovas et al, 1986;Buraczynska et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that apo A-I, together with lecithin -cholesterol acyltransferase, facilitates the removal of cholesterol from peripheral tissues and transports it to the liver for catabolism [2]. Patients with a defective apo A-I gene show low levels of plasma high-density lipoprotein and apo A-I and accelerated atherosclerosis [3]. Several epidemiological studies have established that plasma levels of high-density lipoprotein and apo A-I are negatively correlated with the incidence of coronary heart diseases [4 -61.…”
mentioning
confidence: 99%